AN APPLICATION MODEL OF FINANCIAL TECHNOLOGY CASH WAQF IN MALAYSIA - Nurul Labanihuda Abdull Rahman; Fatin Syazwani Safiyuddin; Raudzatul Jannah Ezahar; Nur Farrah Ain Zainuddin; Nadiah Nabilah Baharum (Journal of Islamic, Social, Economics and Development, 2024)
Over the years, Waqf has made a substantial contribution to the growth of Islamic society as the tradition has persisted. The advantage of cash waqf is it may be managed with greater flexibility and invested in a variety of industries. The collection might be increased if the contributors are aware of Financial Technology (FinTech) services provided by waqf institutions. This study aims to develop a model of financial technology for cash waqf contributions. The researchers discussed the empirical support of various literature that recognizes the use of Theory of Planned Behavior and Theory Acceptance Model (TAM) for measuring the application of FinTech to improve waqf contributions. It is anticipated that the results of this study will broaden our understanding of cash waqf contributions among Malaysian Muslims and at the same time increase cash waqf contributions through FinTech applications.